Talking about learning disability: Discursive acts in managing an ideological dilemma - Victoria Cluley; Alison Pilnick; Rachel Fyson (Elsevier, 2022)
Learning disability is a term that can mean different things to different people. It is also a term that has undergone much revision and critique, being linked to stigma and prejudice. Consequently, talking about learning disability can be a delicate matter. This paper analyses the discursive work done by focus group participants (professionals and lay people in supportive roles) to manage their talk about learning disability. We show how participants drew on six interpretive repertoires, organised as three binary pairs, to negotiate an ideological dilemma associated with stigma and the body. We argue that the participants drew on these repertoires to maintain a particular subject position, the 'good person' subject position, and performed what we call 'passing off' behaviour to manage their talk. We conclude that some aspects of learning disability remain 'unspeakable', and that this has consequences for the policies and practices which determine the support available to people with learning disabilities.